PREDICTION OF THE INFLUENCE OF GEOMETRICAL IMPERFECTION TO LOAD CARRYING CAPACITY OF CONICAL SHELLS UNDER AXIAL LOADING - Özyurt, Erdem; Yilmaz, Haluk; Tomek, Petr (My University, 2018)
In the present study, the effect of geometrical imperfections on the load carrying capacity of conical shells under axial loading was investigated. In accordance with this purpose, limit loads for both ideal and imperfect conical shells were utilized via a series of numerical analysis. Numerical analyses were made for radially constrained conical shells at various shell thicknesses and semi-vertex angles. Thus, it is aimed to evaluate the effect of the geometric imperfections on shells with various geometrical parameters. In all numerical simulations, nonlinear geometry influences were included (GNIA - Geometrically nonlinear analysis with imperfection included). It is found that with increasing semi-vertex angle, the sensitivity of the structures to imperfection also reduces. Shell thickness tshell has almost no effect on the sensitivity to imperfection.
PREDIKCE VLIVU GEOMETRICKÉ IMPERFEKCE NA ÚNOSNOST KUŽELOVÝCH SKOŘEPIN ZATÍŽENÝCH OSOVOU SILOU
Keywords: Conical shell; buckling; axial compression; imperfection; kuželová skořepina; buckling; osová tlaková síla; imperfekce